2016
DOI: 10.1111/etho.12126
|View full text |Cite
|
Sign up to set email alerts
|

Suffering Peacefully: Experiences of Infancy Death in Contemporary Zambia

Abstract: In Ng'ombe Township in Lusaka, the death of a baby is often met with silence. Based on long‐term ethnographic fieldwork, this article explores how the bereaved mother's silence is guided by wider cultural norms and values associated with death, by complex notions of what it means to be a person, and by local perceptions of mental health and well‐being. To enhance the complexity of the mother's silences, it also explores how structures of poverty manifest in mothers’ experiences of loss and how silence may hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As in previous studies, our findings revealed a high risk of intense grief when faced with the loss of a child in cases of violent or sudden death (Djelantik et al, 2020). At the same time, as in previous studies, we found that the environmental conditions in which the bereaved mother lives are key factors in the experience of bereavement after the loss (Silverman et al, 2021;Smørholm, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As in previous studies, our findings revealed a high risk of intense grief when faced with the loss of a child in cases of violent or sudden death (Djelantik et al, 2020). At the same time, as in previous studies, we found that the environmental conditions in which the bereaved mother lives are key factors in the experience of bereavement after the loss (Silverman et al, 2021;Smørholm, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…The culturally sensitive literature draws attention to how culture defines the path individuals follow when grieving (Smørholm, 2016). Studies have emphasized the cultural elements present in the grieving process (Kofod & Brinkmann, 2017; Silverman et al, 2021; Yasien‐Esmael et al, 2020), where the living circumstances of the bereaved were of significant relevance to the extent and manner in which they managed their grief (Harris, 2010; Hemer, 2010; Rothaupt & Becker, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the face of suffering, the effortful work of silence may also help sustain precarious social relations. For some, silence may be the most virtuous-yet incredibly effortful-way of enduring pain and loss (see, for example, Buch Segal 2016;Livingston 2012;Smørholm 2016). Even where narrative utterances like 'you endure' help to constitute enduring pain as virtuous, people may remain silent about some experiences simply because they are impossible to put into words (Throop 2010).…”
Section: Feminist Traditionsmentioning
confidence: 99%
“… 5. For a comprehensive discussion on the universality of the Scheper-Hughes hypothesis that mothers in poor communities with high infant mortality and fertility do not mourn the loss of their babies, see Einarsdottir (2004) and Smørholm (in press). …”
mentioning
confidence: 99%